Accommodating Container Vessels in the Northern Adriatic Ports Through Optimal Feeder Servicing - Twrdy, Elen; Smredu, Ivan (Promet - Traffic&Transportation, 2004)
Maritime traffic, in particular container transport, is experiencingrapid and technologically advanced development oftransport means. This development has led to the constructionof vessels of constantly increasing capacity that transport containersaround the world. Vessels with a capacity of up to18,000 TEU are to be expected and port development will haveto adapt to these trends.This trend will inevitably change conditions in the northernAdriatic, which is lacking the maritime and market conditionsto accommodate large dimension vessels. Hence, the questionis raised whether the northern Adriatic ports will be able to establishconnections that will allow them to maintain their marketshare in relation to western European ports. The solutioncan be provided by an optimal feeder vessel service.